2018
DOI: 10.3390/en11061581
|View full text |Cite
|
Sign up to set email alerts
|

Fly Ash Formation and Characteristics from (co-)Combustion of an Herbaceous Biomass and a Greek Lignite (Low-Rank Coal) in a Pulverized Fuel Pilot-Scale Test Facility

Abstract: The lignite boilers are designed for lower quality fuels, and often the ash is not utilized. This work assessed the impact of combustion of an herbaceous biomass with a low-quality Greek lignite on the quality of the resulting fly ash. Test results were compared with those of fly ash samples from an industrial facility using the same fuel qualities. Inductively coupled plasma-optical (ICP) emission spectroscopy, X-ray powder diffraction (XRD), and scanning electron microscope (SEM) analyses were performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…However, the emission of PM during Zhundong coal combustion, also as an important ash-related problem, has rarely been reported until now. The distinctive coal was reported to emit much more PM 10 (particulate matter with an aerodynamic diameter of ≤10 µm) than other lignite and bituminous coals during combustion [12], which could cause both the operating problem of initial deposition and the environmental problem of haze [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the emission of PM during Zhundong coal combustion, also as an important ash-related problem, has rarely been reported until now. The distinctive coal was reported to emit much more PM 10 (particulate matter with an aerodynamic diameter of ≤10 µm) than other lignite and bituminous coals during combustion [12], which could cause both the operating problem of initial deposition and the environmental problem of haze [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hein and Bemtgen (1998) [17] summed up results from several full scale co-combustion trials, stating that at low biomass share, properties of the ash and fly ash formed resemble those from sole fossil fuel combustion, and though the slagging, fouling, and corrosion tendencies increased, they are at a tolerable level. More recently, results of low quality high ash lignite and herbaceous biomass co-combustion in a 500 kW combustor were presented by Fuller et al (2018) [28], confirming only minor changes in the fly ash composition even at 50% co-combustion biomass share. Kopzyński et al (2017) [127] found that ash from torrefied biomass samples co-combusted with coal exhibits higher initial softening temperatures than that from raw biomass co-combustion.…”
Section: Slagging Fouling Corrosion and Ash Propertiesmentioning
confidence: 79%
“…Biomass and waste co-combustion has been intensely researched in the last decade. Pilot and full scale systems studies conducted several decades ago [17][18][19] continue to be published [20,21], but they are more recently accompanied by laboratory experiments employing drop tube furnaces [22][23][24], thermogravimetric analyses (TGA) [25][26][27], and other laboratory equipment [28,29]. Experience with co-combustion systems operation are reported in the USA [30,31], Europe [32], as well as other parts of the world [33], generally claiming reduction in CO 2 and other greenhouse gases emissions [34] with only minor changes in co-fired power plants and utility boilers thermal efficiencies [35].…”
Section: Introductionmentioning
confidence: 99%
“…The twenty-one published papers cover a variety of biomass or waste residuals that have been converted into different types of energy, biofuels or biochemicals including heat [1,11,16], methane [2,4,[7][8][9]17,[19][20][21], electricity [2,11,16], short chain fatty acids [2,19], ethanol [3,12,19], syngas [5,19], nutrient pellets [6], hydroxymethylfurfura [15], and hydrogen [2,10,14,18,19]. The key information including biomass or residuals, products, and technology for the production and type of research are summarized in Table 1.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…The first contribution by Fuller et al [1] assessed the impact of co-combustion of an herbaceous biomass with low-quality Greek lignite on the quality of the fly ash. The authors compared the results with those of fly ash samples from an industrial facility using the same fuel qualities.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%